A dry electrode and its preparation method and semi-solid battery
Through the dry electrode preparation method, the solvent use and recovery links are eliminated, and the problems of high cost, high energy consumption and low material density in wet electrode preparation are solved, and more efficient and economical electrode preparation is achieved, and the energy density of the battery is improved.
Patent Information
- Application Number
- CN202411987258.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing wet electrode preparation process requires the use of toxic solvent NMP, which leads to high production costs and energy consumption, and the material compaction density is not high, affecting the energy density of the battery.
By using the dry electrode preparation method, the active substance, conductive agent and inorganic solid electrolyte are dry mixed, and then mixed with the binder, the surface of the current collector is covered with roll pressure, eliminating the coating and drying and solvent recovery.
The cost and energy consumption of electrode preparation are reduced, the compaction density of the electrode sheet is improved, cracks and micropore problems are reduced, and the overall energy density of the battery is improved.
Smart Images

Figure BDA0005222867050000131 
Figure BDA0005222867050000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a dry electrode and a preparation method thereof and a semi-solid battery. Background Art
[0002] Electrodes are the core components of lithium batteries, and they play a key role in the battery's charge and discharge process. Electrodes control the embedding and de-embedding process of lithium ions, and are also the key parts of electronic conduction. Electrodes include positive and negative electrodes, and the working principle of lithium batteries is mainly based on the embedding and de-embedding process of lithium ions between the positive and negative electrodes. During charging, lithium ions are extracted from the positive electrode material, migrate to the negative electrode through the electrolyte, and embed into the negative electrode material; during discharge, the opposite is true, lithium ions are extracted from the negative electrode, and return to the positive electrode through the electrolyte. In this process, electrons flow in the external circuit, thereby generating current to power external devices.
[0003] Electrodes are usually prepared using a wet process, which includes coating, drying, and solvent recovery, accounting for 22.76% and 53.99% of manufacturing costs and energy costs, respectively. In addition, the solvent NMP (N-methylpyrrolidone) required for the positive electrode ingredients is toxic and environmentally unfriendly. It needs to be recycled in the traditional wet process, and the recycling process consumes a lot of energy. After the solvent evaporates in the wet electrode, many gaps will be left between the active material and the conductive agent particles, and the gaps will cause the compaction density of the material to be low.
[0004] Therefore, there is an urgent need to provide a solution that does not require the use of solvents and can save the coating drying and solvent recovery steps, thereby reducing costs and energy consumption, while increasing the compaction density. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a dry electrode and a preparation method thereof and a semi-solid battery. The dry electrode provided by the present invention does not require a solvent during preparation, can omit the coating drying and solvent recovery steps, and has a simpler process flow, thereby reducing costs and energy consumption. In addition, there is no drying process during preparation, so there is no gap left after the solvent evaporates. The active material, the conductive agent and the inorganic solid electrolyte particles are in close contact, which can effectively improve the compaction density of the electrode plate and reduce problems such as cracks and micropores, thereby improving the overall energy density.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a dry electrode, comprising a current collector and a dry membrane arranged on at least one side of the current collector; the dry membrane comprises the following components by mass fraction: 95% to 97.5% of active material; 0.5% to 1% of conductive agent; 1% to 2% of inorganic solid electrolyte; 1% to 3% of binder; the sum of the mass fractions of the above components is 100%.
[0008] The mass fraction of the active material can be, for example, 95%, 96%, 97% or 97.5%; the mass fraction of the conductive agent can be, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%; the mass fraction of the inorganic solid electrolyte can be, for example, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%; the mass fraction of the binder can be, for example, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0009] The present invention provides a dry electrode, which does not require a solvent when prepared, can omit the coating drying and solvent recovery steps, has a simpler process flow, thereby reducing costs and energy consumption, and has a smaller equipment footprint, making it more suitable for large-scale production of electrode plates.
[0010] The dry electrode provided by the present invention does not involve a drying process during preparation, so there are no gaps left after solvent evaporation. The active material, conductive agent and inorganic solid electrolyte particles are in close contact, which can effectively increase the compaction density of the electrode plate and reduce problems such as cracks and micropores, thereby improving the overall energy density.
[0011] The dry electrode provided by the present invention has an inorganic solid electrolyte mixed in the dry film, which is helpful to form a high-quality SEI / CEI film, induce the capacity of the active material to be exerted, improve the cycle stability, and reduce the amount of electrolyte used; when the contents of the active material, the conductive agent, the inorganic solid electrolyte and the binder meet the specified range, the conductive agent and the inorganic solid electrolyte are evenly dispersed between the pores of the active material, and a three-dimensional electronic conductive network and an ion conductive network are established respectively, which can improve the electron and ion transmission rate; the binder makes the components and the components and the current collector tightly bonded, which can reduce the interface contact impedance and prevent the active material from peeling off from the current collector to cause capacity failure.
[0012] Preferably, the active material is a positive electrode active material or a negative electrode active material.
[0013] In the present invention, the active material can be a positive electrode active material or a negative electrode active material, and correspondingly, the dry electrode can be a dry positive electrode or a dry negative electrode.
[0014] The present invention does not limit the specific type of the positive electrode active material, including but not limited to lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide or lithium titanate.
[0015] The present invention does not limit the specific type of negative electrode active material, including but not limited to graphite and / or silicon-carbon materials.
[0016] Preferably, the conductive agent comprises a carbon material.
[0017] The present invention does not limit the specific types of carbon materials, including but not limited to conductive carbon black, conductive graphite, carbon nanotubes or graphene.
[0018] Preferably, the inorganic solid electrolyte includes at least one of LATP, LLTO and LLZO.
[0019] Preferably, the particle size D50 of the inorganic solid electrolyte is 100-300 μm, for example, 100 μm, 150 μm, 200 μm, 250 μm or 300 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] In the dry electrode of the present invention, if the particle size of the inorganic solid electrolyte is too large, the specific surface area is large and the reactive sites are few, which is not conducive to promoting the forward chemical reaction inside the electrode; if the particle size of the inorganic solid electrolyte is too small, the capacity will agglomerate and the dispersion will be uneven during the dispersion process.
[0021] Preferably, the binder comprises polytetrafluoroethylene (PTFE).
[0022] Preferably, the current collector comprises a foil material and a conductive layer covering a surface of the foil material, and the conductive layer is in contact with the dry film.
[0023] In the present invention, the current collector having a conductive layer is used to reduce the interface impedance between the current collector and the active material.
[0024] In a second aspect, the present invention provides a method for preparing the dry electrode according to the first aspect, the preparation method comprising:
[0025] (1) The active material, the conductive agent and the inorganic solid electrolyte are first mixed to obtain a first mixture.
[0026] (2) A binder and the first mixture are mixed for a second time to obtain a second mixture.
[0027] (3) Performing a fiberization treatment on the second mixture to obtain a fiberized mixture.
[0028] (4) Rolling and pressing the fiberized mixture onto at least one side of the current collector to obtain a dry electrode.
[0029] The present invention firstly mixes the active material, the conductive agent and the inorganic solid electrolyte evenly, then mixes them with the binder, forms a self-supporting film under the fibrillation action of the binder, and finally rolls and covers the surface of the current collector to obtain a dry electrode.
[0030] Preferably, the first mixing method includes ball milling, the orbital speed of the ball mill is 10 to 30 rpm, for example, it can be 10 rpm, 15 rpm, 20 rpm, 25 rpm or 30 rpm, etc.; the rotation speed is 400 to 600 rpm, for example, it can be 400 rpm, 450 rpm, 500 rpm, 550 rpm or 600 rpm, etc.; the time is 10 to 20 min, for example, it can be 10 min, 12 min, 15 min, 18 min or 20 min, etc., but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] In the present invention, low-speed stirring and dispersion is performed during the first mixing.
[0032] Preferably, the second mixing method includes ball milling, the revolution speed of the ball mill is 10 to 20 rpm, for example, it can be 10 rpm, 12 rpm, 15 rpm, 18 rpm or 20 rpm, etc.; the time is 5 to 15 min, for example, it can be 5 min, 8 min, 10 min, 12 min or 15 min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In the present invention, low-speed pre-stirring is performed during the second mixing.
[0034] Preferably, the fiberization treatment method includes ball milling, the orbital speed of the ball mill is 20 to 30 rpm, for example, it can be 20 rpm, 22 rpm, 25 rpm, 28 rpm or 30 rpm, etc.; the rotation speed is 1400 to 1600 rpm, for example, it can be 1400 rpm, 1450 rpm, 1500 rpm, 1550 rpm or 1600 rpm, etc.; the time is 50 to 80 min, for example, it can be 50 min, 60 min, 70 min or 80 min, etc., but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] The present invention utilizes high-speed shearing force to fiberize the binder.
[0036] In a third aspect, the present invention provides a semi-solid-state battery, wherein the positive electrode and / or negative electrode in the semi-solid-state battery is the dry electrode described in the first aspect, or a dry electrode prepared by the preparation method described in the second aspect.
[0037] Preferably, the semi-solid battery further comprises a separator for separating the positive electrode and the negative electrode.
[0038] Preferably, the diaphragm includes a base film, the base film having a first surface and a second surface arranged opposite to each other, the first surface facing the positive electrode; an inorganic solid electrolyte coating and a first polymer coating are arranged in sequence on the first surface in a direction away from the base film; and a second polymer coating is arranged on the second surface.
[0039] Compared with liquid batteries, semi-solid batteries have a reduced electrolyte content or the electrolyte is in a gel state. Its ion conductivity is often an order of magnitude lower than that of liquid electrolytes. The difficulty of lithium ion diffusion increases. The slowness of ion diffusion leads to a large concentration polarization during the charge and discharge process, resulting in a large battery DCR and poor rate performance, making it difficult to support high-rate charge and discharge. In addition, semi-solid batteries have poor performance at low temperatures, low low-temperature discharge capacity, and the risk of lithium precipitation during charging. At low temperatures, liquid electrolytes can reduce the freezing point of the electrolyte by regulating the solvent composition, but the glass transition temperature of gel polymer electrolytes is low. At low temperatures, lithium ions are even more confined in polymer molecules with a cross-linked spatial network structure, so the ion conductivity drops sharply. Compared with pure liquid systems, semi-solid batteries have lower low-temperature discharge capacity and are more prone to lithium precipitation during low-temperature charging.
[0040] The present invention arranges an inorganic solid electrolyte coating on the surface of the base film, and uses the inorganic solid electrolyte as an ion conductive agent, so that the diaphragm forms a continuous ion conductive channel, which can effectively reduce polarization, reduce internal resistance, and is beneficial to improving low temperature performance and rate performance.
[0041] In the diaphragm of the present invention, the role of arranging polymer coatings on both sides is to realize the basic function of bonding the pole piece and the diaphragm together, and improve the forming performance of the battery cell, that is, the hardness of the battery cell; at the same time, the pole piece and the diaphragm are bonded together, which significantly improves the interface flatness and inhibits the deformation of the battery cell.
[0042] Preferably, the inorganic solid electrolyte coating comprises an inorganic solid electrolyte and a binder, and the inorganic solid electrolyte comprises at least one of LATP, LLTO and LLZO.
[0043] In the inorganic solid electrolyte coating of the present invention, the inorganic solid electrolyte is preferably LATP. In addition to enabling the diaphragm to form a continuous ion conductive channel, the reaction activity of LATP with Li can effectively inhibit the growth of lithium dendrites.
[0044] Preferably, the inorganic solid electrolyte coating and the inorganic solid electrolyte in the dry electrode are of the same type.
[0045] Preferably, in the inorganic solid electrolyte coating, the particle size D50 of the inorganic solid electrolyte is 0.5 to 1.5 μm, for example, it can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm or 1.5 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In the present invention, when the particle size of the inorganic solid electrolyte meets the preferred range, it is more conducive to the formation of a continuous ion conductive channel in the diaphragm. If the particle size of the inorganic solid electrolyte is too large, the coating thickness is large and difficult to reduce, which is not conducive to the overall energy density of the battery cell, and the large particle size leads to a small coating weight and a large thermal shrinkage of the diaphragm; if the particle size of the inorganic solid electrolyte is too small, it is easy to block the pores on the base film, resulting in an increase in the air permeability value, which is not conducive to lithium ion transmission.
[0047] Preferably, the binder in the inorganic solid electrolyte coating includes at least one of polyacrylate (ACM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyvinyl pyrrolidone (PVP), polyethylene oxide (PEO), polyvinyl alcohol (PVA) and sodium carboxymethyl cellulose (CMC).
[0048] Preferably, in the inorganic solid electrolyte coating, the mass ratio of the inorganic solid electrolyte to the binder is (7-10):1, for example, it can be 7:1, 8:1, 9:1 or 10:1, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] Preferably, the thickness of the inorganic solid electrolyte coating is 1 to 3 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] Preferably, the first polymer coating and the second polymer coating are each independently a polymethyl methacrylate (PMMA) coating or a polyvinylidene fluoride (PVDF) coating.
[0051] It should be noted that the types of polymers in the first polymer coating and the second polymer coating may be the same or different.
[0052] Preferably, the thickness of the polymethyl methacrylate coating is 0.5-1 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] Preferably, the thickness of the polyvinylidene fluoride coating is 1 to 2 μm, for example, it can be 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In the present invention, if the first polymer coating and / or the second polymer coating is too thick, it is easy to cause pore blockage in the diaphragm, which is not conducive to lithium ion transmission; if the first polymer coating and / or the second polymer coating is too thin, the bonding strength between the diaphragm and the electrode piece is reduced, and it is impossible to bond with the electrode piece to improve the hardness of the battery cell.
[0055] Preferably, when the polymer types in the first polymer coating and the second polymer coating are the same, the thicknesses of the first polymer coating and the second polymer coating are the same.
[0056] Preferably, the semi-solid battery also includes an electrolyte.
[0057] Preferably, the weight of the electrolyte accounts for 5-10% of the total weight of the semi-solid state battery, for example, it may be 5%, 6%, 7%, 8%, 9% or 10%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] It should be noted that the total weight of the semi-solid battery refers to the sum of the masses of the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte, and the outer shell (aluminum-plastic film).
[0059] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0060] Compared with the prior art, the present invention has the following beneficial effects:
[0061] The present invention provides a dry electrode, which does not require a solvent when prepared, can omit the coating drying and solvent recovery steps, has a simpler process flow, thereby reducing costs and energy consumption, and has a smaller equipment footprint, making it more suitable for large-scale production of electrode plates.
[0062] The dry electrode provided by the present invention does not involve a drying process during preparation, so there are no gaps left after solvent evaporation. The active material, conductive agent and inorganic solid electrolyte particles are in close contact, which can effectively increase the compaction density of the electrode plate and reduce problems such as cracks and micropores, thereby improving the overall energy density.
[0063] The dry electrode provided by the present invention has an inorganic solid electrolyte mixed in the dry film, which is helpful to form a high-quality SEI / CEI film, induce the capacity of the active material to be exerted, improve the cycle stability, and reduce the amount of electrolyte used; when the contents of the active material, the conductive agent, the inorganic solid electrolyte and the binder meet the specified range, the conductive agent and the inorganic solid electrolyte are evenly dispersed between the pores of the active material, and a three-dimensional electronic conductive network and an ion conductive network are established respectively, which can improve the electron and ion transmission rate; the binder makes the components and the components and the current collector tightly bonded, which can reduce the interface contact impedance and prevent the active material from peeling off from the current collector to cause capacity failure. DETAILED DESCRIPTION
[0064] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0065] Example 1
[0066] This embodiment provides a dry-process positive electrode, including a current collector and a dry-process membrane disposed on both side surfaces of the current collector.
[0067] The current collector is an aluminum foil coated with carbon layers on both sides.
[0068] Calculated by mass fraction, the dry process membrane includes the following components: 96.5% active material; 0.5% conductive agent; 1% LATP; 2% PTFE; wherein the active material is lithium cobalt oxide, the conductive agent is Super P and carbon nanotubes in a mass ratio of 1:1, and the LATP particle size D50 is 200nm.
[0069] This embodiment also provides a method for preparing the above-mentioned dry-process positive electrode, comprising the following steps:
[0070] (1) Lithium cobalt oxide, Super P, carbon nanotubes and LATP are ball-milled at an orbital speed of 20 rpm and an autorotational speed of 500 rpm for 15 min to obtain a first mixture.
[0071] (2) ball milling the PTFE and the first mixture at an orbital speed of 15 rpm for 10 min to obtain a second mixture.
[0072] (3) The second mixture is subjected to a fiberization treatment by ball milling, wherein the orbital speed of the ball mill is 25 rpm, the rotation speed is 1500 rpm, and the time is 60 min, and a fiberized mixture is obtained after completion.
[0073] (4) The fiberized mixture is rolled and covered on both sides of the current collector to obtain a dry positive electrode.
[0074] This embodiment further provides a dry-process negative electrode, including a current collector and a dry-process membrane disposed on both side surfaces of the current collector.
[0075] The current collector is a copper foil coated with carbon layers on both sides.
[0076] The dry process membrane comprises the following components by mass fraction: 96.5% active material; 0.5% conductive agent; 1% LATP; 2% PTFE; wherein the active material is graphite, the conductive agent is Super P and carbon nanotubes in a mass ratio of 1:1, and the LATP particle size D50 is 200nm.
[0077] This embodiment also provides a method for preparing the above-mentioned dry-process negative electrode, comprising the following steps:
[0078] (1) Graphite, Super P, carbon nanotubes and LATP are ball-milled at an orbital speed of 20 rpm and an autorotational speed of 500 rpm for 15 min to obtain a first mixture.
[0079] (2) ball milling the PTFE and the first mixture at an orbital speed of 15 rpm for 10 min to obtain a second mixture.
[0080] (3) The second mixture is subjected to a fiberization treatment by ball milling, wherein the orbital speed of the ball mill is 25 rpm, the rotation speed is 1500 rpm, and the time is 60 min, and a fiberized mixture is obtained after completion.
[0081] (4) The fiberized mixture is rolled and covered on both sides of the current collector to obtain a dry-process negative electrode.
[0082] Example 2
[0083] The difference between this embodiment and embodiment 1 is that the particle size D50 of LATP in the dry-process positive electrode is 800 nm; the particle size D50 of LATP in the dry-process negative electrode is 800 nm.
[0084] The remaining parameters remain the same as those in Example 1.
[0085] Example 3
[0086] The difference between this embodiment and embodiment 1 is that the particle size D50 of LATP in the dry-process positive electrode is 50 nm; the particle size D50 of LATP in the dry-process negative electrode is 50 nm.
[0087] The remaining parameters remain the same as those in Example 1.
[0088] Comparative Example 1
[0089] The difference between this embodiment and embodiment 1 is that in the dry-process positive electrode and the dry-process negative electrode membranes, the mass fraction of the active material is adjusted to 93.5%, the mass fraction of the conductive agent is adjusted to 1.5%, and the mass fraction of LATP is adjusted to 3%.
[0090] The remaining parameters remain the same as those in Example 1.
[0091] Comparative Example 2
[0092] The difference between this embodiment and embodiment 1 is that in the dry-process positive electrode and the dry-process negative electrode membranes, the mass fraction of the active material is adjusted to 97.8%, the mass fraction of the conductive agent is adjusted to 0.2%, and LATP is not added.
[0093] The remaining parameters remain the same as those in Example 1.
[0094] Application Example 1
[0095] This application example provides a semi-solid battery, which includes an aluminum-plastic film, in which a winding core formed by a positive electrode, a separator and a negative electrode is installed. The positive electrode and the negative electrode are the dry-process positive electrode and the dry-process negative electrode provided in Example 1, respectively.
[0096] The diaphragm includes a PE base film, the PE base film has a first surface and a second surface arranged opposite to each other, the first surface faces the positive electrode; an inorganic solid electrolyte coating and a PMMA coating are sequentially arranged on the first surface in a direction away from the base film; a PMMA coating is arranged on the second surface; wherein the inorganic solid electrolyte coating includes LATP and polyacrylate binder, the LATP particle size D50 is 1 μm, and the mass ratio of LATP to polyacrylate is 9:1; the thickness of the inorganic solid electrolyte coating is 2 μm; and the thickness of the PMMA coating on both sides is 0.5 μm.
[0097] The semi-solid battery also contains an electrolyte, and the weight of the electrolyte accounts for 8% of the total weight of the semi-solid battery.
[0098] This application example also provides a method for preparing the above-mentioned semi-solid battery, comprising the following steps:
[0099] The positive electrode, separator and negative electrode are assembled in sequence to obtain a roll core; then, after packaging and baking, liquid is injected, followed by chemical composition and capacity sorting processes to complete the battery production and obtain a semi-solid-state battery.
[0100] Application Example 2-3
[0101] The difference from Application Example 1 is that the dry-process positive electrode and dry-process negative electrode provided in Example 1 are replaced by the dry-process positive electrode and dry-process negative electrode provided in Example 2 and the dry-process positive electrode and dry-process negative electrode provided in Example 3 respectively.
[0102] The remaining parameters are the same as those in Application Example 1.
[0103] Application Example 4
[0104] The difference between this application example and application example 1 is that in the inorganic solid electrolyte coating of the diaphragm, the LATP particle size D50 is 2 μm.
[0105] The remaining parameters are the same as those in Application Example 1.
[0106] Application Example 5
[0107] The difference between this application example and application example 1 is that in the inorganic solid electrolyte coating of the diaphragm, the LATP particle size D50 is 0.4 μm.
[0108] The remaining parameters are the same as those in Application Example 1.
[0109] Application Example 6
[0110] The difference between this application example and application example 1 is that the thickness of the PMMA coating on both sides of the diaphragm is 2 μm.
[0111] The remaining parameters are the same as those in Application Example 1.
[0112] Comparative Application Example 1-2
[0113] The difference from Application Example 1 is that the dry-process positive electrode and dry-process negative electrode provided in Example 1 are replaced by the dry-process positive electrode and dry-process negative electrode provided in Comparative Example 1 and the dry-process positive electrode and dry-process negative electrode provided in Comparative Example 2 respectively.
[0114] The remaining parameters are the same as those in Application Example 1.
[0115] Performance Testing
[0116] The following tests were performed on the semi-solid batteries provided in the above application examples and comparative application examples:
[0117] (1) DCR test:
[0118] At 50% SOC voltage, use 0.02C current (I1) to discharge for 10s, the test voltage is recorded as V1, and then use 1C current (I2) to discharge for 1s and the voltage is recorded as V2. DCR = (V1-V2) / (I2-I1).
[0119] (2) Rate performance test:
[0120] At room temperature, charge at a constant current of 0.5C to the full charge voltage, then charge at a constant voltage until the current is ≤0.025C; then discharge at a current of 0.2C until the voltage is cut off at 3.0V, and record the discharge capacity at 0.2C.
[0121] Under room temperature conditions, the batteries were charged at a constant current of 0.5C to the full charge voltage, and then charged at a constant voltage to a current ≤ 0.025C; they were then discharged at a current of 2C to a cutoff of 3.0V, and the 2C discharge capacity was recorded.
[0122] Calculate the 2C / 0.2C discharge rate = 2C discharge capacity / 0.2C discharge capacity.
[0123] (3) Low temperature performance test:
[0124] ① Low temperature discharge capacity test:
[0125] 1) After fully charging the battery, place it in an environment of 25℃±2℃ and discharge it at 0.2C to a final voltage of 3.0V, and record the discharge capacity. 2) After fully charging the battery, place it in an environment of -20℃±2℃ for 4h, then discharge it at 0.2C to a final voltage of 3.0V, and record the discharge capacity. 3) Calculate the 0.2C discharge capacity at -20℃ / 0.2C discharge capacity at 25℃.
[0126] ② Test of lithium deposition during low temperature charging:
[0127] After placing the battery cell in a 0℃±3℃ environment for 240 minutes, charge it at a constant current of 0.5C to the limited charging voltage, then charge it at a constant voltage until the current drops to 0.025C and stop charging; leave it for 10 minutes, then discharge it at a current of 0.5C to 3.0V. Repeat the above steps 50 times, and the discharge capacity in the 50th week / the discharge capacity in the first week is the cycle capacity retention rate; then fully charge the battery cell and disassemble it to confirm the lithium deposition at the negative electrode interface.
[0128] The test results are shown in Table 1.
[0129] Table 1
[0130]
[0131]
[0132] analyze:
[0133] It can be seen from Application Example 1 that the semi-solid battery assembled using the dry-process positive electrode and the dry-process negative electrode of the present invention has a low internal resistance and excellent rate performance and low-temperature performance.
[0134] It can be seen from Application Examples 1 and 2-3 that if the LATP particle size in the positive electrode of the several-method method and the dry-method negative electrode is too large, the specific surface area is large and the reaction active sites are few, which is not conducive to promoting the forward chemical reaction inside the electrode, resulting in a decrease in the performance of the semi-solid-state battery; if the LATP particle size in the positive electrode of the several-method method and the dry-method negative electrode is too small, the capacity will agglomerate and the dispersion will be uneven during the dispersion process, resulting in a decrease in the final performance of the semi-solid-state battery.
[0135] It can be seen from Application Examples 1 and 4-5 that in the inorganic solid electrolyte coating of the diaphragm, if the LATP particle size is too large, the coating thickness is large and difficult to reduce, which is not conducive to the overall energy density of the battery cell, and the large particle size leads to a small coating weight, and the diaphragm shrinks greatly, which reduces the performance of the semi-solid battery; if the LATP particle size is too small, it is easy to clog the pores on the base membrane, resulting in an increase in the permeability value, which is not conducive to lithium ion transmission and reduces the performance of the semi-solid battery.
[0136] It can be seen from Application Examples 1 and 6 that if the thickness of the PMMA coating on both sides of the diaphragm is too large, it is easy to cause pore blockage in the diaphragm, which is not conducive to lithium ion transmission and reduces the performance of the semi-solid-state battery.
[0137] It can be seen from Application Example 1 and Comparative Application Examples 1-2 that in the membranes of several-method positive electrodes and dry-method negative electrodes, the content of conductive agent is relatively high, the content of LATP is relatively high, and the content of active substances is relatively low, which will lead to a decrease in the performance of the semi-solid-state battery; in the membranes of several-method positive electrodes and dry-method negative electrodes, the content of conductive agent is relatively low, and LATP is not added, which increases the content of active substances, leading to a decrease in the performance of the semi-solid-state battery.
[0138] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A dry electrode, characterized in that: The dry electrode comprises a current collector and a dry membrane disposed on at least one side surface of the current collector; The dry-process membrane comprises the following components by mass fraction: 95% to 97.5% of active material; 0.5% to 1% of conductive agent; 1% to 2% of inorganic solid electrolyte; and 1% to 3% of binder; the sum of the mass fractions of the above components is 100%.
2. The dry electrode according to claim 1, characterized in that: The active material is a positive electrode active material or a negative electrode active material; Preferably, the conductive agent comprises a carbon material; Preferably, the inorganic solid electrolyte comprises at least one of LATP, LLTO and LLZO; Preferably, the particle size D50 of the inorganic solid electrolyte is 100 to 300 nm; Preferably, the binder comprises polytetrafluoroethylene; Preferably, the current collector comprises a foil material and a conductive layer covering a surface of the foil material, and the conductive layer is in contact with the dry film.
3. A method for preparing a dry electrode according to claim 1 or 2, characterized in that: The preparation method comprises: (1) performing a first mixing of the active material, the conductive agent and the inorganic solid electrolyte to obtain a first mixture; (2) performing a second mixing of the binder and the first mixture to obtain a second mixture; (3) performing a fiberization treatment on the second mixture to obtain a fiberized mixture; (4) Rolling the fiberized mixture to cover at least one side of the current collector to obtain a dry electrode.
4. The preparation method according to claim 3, characterized in that: The first mixing method includes ball milling, the orbital speed of the ball mill is 10 to 30 rpm, the rotation speed is 400 to 600 rpm, and the time is 10 to 20 minutes.
5. The preparation method according to claim 3 or 4, characterized in that: The second mixing method includes ball milling, the revolution speed of the ball mill is 10 to 20 rpm, and the time is 5 to 15 minutes.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The fiberization treatment method includes ball milling, the orbital speed of the ball mill is 20-30 rpm, the rotation speed is 1400-1600 rpm, and the time is 50-80 minutes.
7. A semi-solid battery, characterized in that: The positive electrode and / or negative electrode in the semi-solid battery is the dry electrode according to claim 1 or 2, or a dry electrode prepared by the preparation method according to any one of claims 3 to 6.
8. The semi-solid-state battery according to claim 7, characterized in that: The semi-solid battery also includes a separator for separating the positive electrode and the negative electrode; Preferably, the diaphragm includes a base film, the base film having a first surface and a second surface arranged opposite to each other, the first surface facing the positive electrode; an inorganic solid electrolyte coating and a first polymer coating are arranged in sequence on the first surface in a direction away from the base film; and a second polymer coating is arranged on the second surface.
9. The semi-solid-state battery according to claim 7 or 8, characterized in that: The inorganic solid electrolyte coating includes an inorganic solid electrolyte and a binder, and the inorganic solid electrolyte includes at least one of LATP, LLTO and LLZO; Preferably, the inorganic solid electrolyte coating and the inorganic solid electrolyte in the dry electrode are of the same type; Preferably, in the inorganic solid electrolyte coating, the particle size D50 of the inorganic solid electrolyte is 0.5 to 1.5 μm; Preferably, in the inorganic solid electrolyte coating, the mass ratio of the inorganic solid electrolyte to the binder is (7-10):1; Preferably, the thickness of the inorganic solid electrolyte coating is 1 to 3 μm; Preferably, the first polymer coating and the second polymer coating are each independently a polymethyl methacrylate coating or a polyvinylidene fluoride coating; Preferably, the thickness of the polymethyl methacrylate coating is 0.5 to 1 μm; Preferably, the thickness of the polyvinylidene fluoride coating is 1-2 μm.
10. The semi-solid-state battery according to any one of claims 7 to 9, characterized in that: The semi-solid battery also includes an electrolyte; Preferably, the weight of the electrolyte accounts for 5-10% of the total weight of the semi-solid battery.
Citation Information
Cited By
Preparation method of solid anode strip with high stability and low interface impedance
CN121076080A
A method for preparing a solid-state anode sheet with high stability and low interfacial impedance
CN121076080B